PARTISIPASI KELUARGA TERHADAP PEMBELAJARAN ONLINE DAN OFFLINE SISWA SD/MI SELAMA COVID-19 - Zakki, Mohammad (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2021)
Learning in education is an activity where educators help and motivate students so that ongoing learning activities occur. learning during vacation time Covid-19 is carried out at the home of each student by online and offline way. In this activity, students cannot carry out learning effectively because of the lack of family participation, the influence of the friendship environment and game addiction in technology. So the tasks given by educational institutions are very far from the expected expectations. This reasech was conducted in the village Lebbek Pakong Pamekasan, wile the objectives of this study are:1. to find out the family's participation in the child's activity in carrying out online / offline tasks2. know the interest in studying students during school holidays, and3. determine the effect of technology on the effectiveness of learning. The research method used is qualitative research. While the results of the study are:1. families, especially both parents, are less supportive of children's learning activities at home during covid holidays 19 and are unable to create a home as an effective and enjoyable learning class.2. only a small number of students carry out learning tasks, both online and offline, and3. students are obsessed with the entertainment available in technology, so that learning activities are not effective.